High particulate carbon deposition in Lhasa—a typical city in the Himalayan–Tibetan Plateau due to local contributions. (May 2020) - Yan, Fangping; Wang, Pengling; Kang, Shichang; Chen, Pengfei; Hu, Zhaofu; Han, Xiaowen; Sillanpää, Mika; Li, Chaoliu
Abstract: The Himalayan–Tibetan Plateau is a typical remote region with sparse air pollution. However, air pollution in cites of the inner Himalayan–Tibetan Plateau is relatively serious due to emissions from local residents. Carbonaceous aerosols are not only an important component of air pollutants that affect the health of local residents but also an important trigger of climate change. In this study, the annual wet and dry deposition rates of carbonaceous particles were investigated in Lhasa—a typical city in the Himalayan–Tibetan Plateau, by collecting precipitation and dry deposition samples and analyzing with a thermal-optical measurement protocol. The results showed that the in-situ annual wet deposition rates of water-insoluble organic carbon (WIOC) and black carbon (BC) were 169.6 and 19.4 mg m −2 yr −1, respectively, with the highest and lowest values occurring in the monsoon and non-monsoon periods, respectively. Both precipitation amounts and concentrations of WIOC and BC contributed to wet deposition rates. The dry deposition rates of WIOC and BC in Lhasa had an opposite seasonal variation to that of wet deposition, with annual average deposition rates of 2563.9 and 165.7 mg m −2 yr −1, respectively, which were much higher than those of the nearby glacier region and remote area. These values were also much higher than the results from modeling and empirical calculations, indicating that Lhasa is a high pollution point that cannot capture by models. The results in this study have significant implications for the transport of local emissions in Lhasa to the nearby remote and glacier regions. Graphical abstract: Image 105 Highlights: High in-situ black and organic carbon deposition rates were reported in Lhasa. High deposition rates were mainly resulted from local emissions in Lhasa. Dry deposition is more important than wet deposition in Lhasa particle scavenging.